Pericoronary adipose tissue for predicting long-term outcomes - van Rosendael; Sophie E; Kamperidis, Vasileios; Maaniitty, Teemu; de Graaf; Michiel A; Saraste, Antti; McKay-Goodall, George E; Jukema, J Wouter; Knuuti, Juhani; Bax, Jeroen J (Oxford University Press, 2025)
Aims
Pericoronary adipose tissue (PCAT) attenuation obtained by coronary computed tomography angiography (CCTA) has been associated with coronary inflammation and outcomes. Whether PCAT attenuation is predictive of major adverse cardiac events (MACE) during long-term follow-up is unknown.
Methods and results
Symptomatic patients with coronary artery disease (CAD) who underwent CCTA were included, and clinical outcomes were evaluated. PCAT was measured at all lesions for all three major coronary arteries using semi-automated software. A comparison between patients with and without MACE was made on both a per-lesion and a per-patient level. The predictive value of PCAT attenuation for MACE was assessed in Cox regression models. In 483 patients (63.3 ± 8.5 years, 54.9% men), 1561 lesions were analysed over a median follow-up duration of 9.5 years. The mean PCAT attenuation was not significantly different between patients with and without MACE. At a per-patient level, the adjusted hazard ratio (HR) and 95% confidence interval (CI) for MACE were 0.970 (95% CI: 0.933–1.008, P = 0.121) when the average of all lesions per patient was analysed, 0.992 (95% CI: 0.961–1.024, P = 0.622) when only the most obstructive lesion was evaluated, and 0.981 (95% CI: 0.946–1.016, P = 0.285) when only the lesion with the highest PCAT attenuation per individual was evaluated. Adjusted HRs for vessel-specific PCAT attenuation in the right coronary artery, left anterior descending artery, and left circumflex artery were 0.957 (95% CI: 0.830–1.104, P = 0.548), 0.989 (95% CI: 0.954–1.025, P = 0.550), and 0.739 (95% CI: 0.293–1.865, P = 0.522), respectively, in predicting long-term MACE.
Conclusion
In patients referred to CCTA for clinically suspected CAD, PCAT attenuation did not predict MACE during long-term follow-up.